Processing of rice husk tobio-silica nanoparticlesthrough thermal combustion - Mahmud, A. (Asian Research Publishing Network, 2016)
High silica content makes rice husk an important non-metallicprecursor for silica nano particle production that worth researchers attraction. Moreover, rice husk is considered to be cost-effective and widely available agro waste bioresource. In this investigation, bio-silica nanoparticles were produced using rice husk as precursor. Under reflux heating, the husks were acid pretreated to remove inorganic impurities and induce the hydrolysis of organic substances. Residual solid husks from the acid pretreatment were thencalcinedat973K.Morphology and non-crystal structure of the biosilica nanoparticles was analysed by TEM and XRD. An aggregate of primary particles having amorphous structure was seen with detection of negligible impurities. This was confirmed by the EDX elemental profile of Si and O as the observed peaks which indicate high purity of the generated silica nanoparticles. This also corroborated the XRF result of 99.761 SiO2.BET surface area of 234.6380m2/g with a pore diameter of 5.3304nm were obtained from the analysis. This characterized the silica nanoparticles to be of high surface area. Â© 2006-2016 Asian Research Publishing Network (ARPN).